BENTUK PENERAPAN SISTEM NEGARA HUKUM PADA JAMAN KLASIK (JAMAN YUNANI KUNO DAN JAMAN ROMAWI KUNO) - WIJAYA, MADE HENDRA (Kerta Dyatmika, 2015)
ABSTRACTÂ Â Â Â Â Â Â Â  This research is titled â??Implementation Form of Rule of Law in the Classic Ages (Ancient Greek and Rome Ancient)â?, with using background about Rule of Law system and theory from the Dicey, Stahl and Brian Z Tamanaha, toÂ  knowing regarding how implementation from the ancient people to use the mind the rule of law. with the purpose how can we later to get using comparatively to implementation from ancient people with modern people forÂ  currently.Â Â Â Â Â Â Â  This research have two problem, the Â first is How does Implementation form rule of law in Ancient Greek, and the second is How does Implementation form of Rule of Law in Rome Ancient. This research method using is normative law which using the legal research that examines the written laws of various aspects, ie: Theory, History, philosophy, with using history approach.Â Â Â Â Â Â Â  In this research found that Greek andÂ  Rome ancient using implementation rule of law, that look inÂ  greek and rome ancient using implementation rule by law not rule by man, and implementation the separate power, Â in implementing their governments, Â their officials and their Â judges are bound by law.Â Keywords : Â implementation, Rule of Law,ancient Greek, ancient Rome Â